Lignocellulosic nanofibril aerogel via gas phase coagulation and diisocyanate modification for solvent absorption. (15th February 2022) - Bian, Huiyang; Duan, Sheng; Wu, Jin; Fu, Yanqiao; Yang, Weisheng; Yao, Shuangquan; Zhang, Zhen; Xiao, Huining; Dai, Hongqi; Hu, Chaoquan
Abstract: Cellulose-based aerogels are considered to be carriers that can absorb oils and organic solvents owing to the merits of low density and high surface area. However, the natural hydrophility and poor mechanical strength often obstruct their widespread applications. In this work, Miscanthus -based dual cross-linked lignocellulosic nanofibril (LCNF) aerogels were prepared by gas phase coagulation and methylene diphenyl dissocyanate (MDI) modification. Due to physical and chemical cross-linking strategies, the optimally 4 M-LCNF aerogels had high surface area of 157.9 m 2 /g, water contact angle of 138.1°, and enhanced compression properties. Moreover, the modified aerogels exhibited absorption performance for various organic solvents, and the maximal absorption capacity of chloroform was 42 g/g aerogel. Because LCNF was directly produced from Miscanthus without using bleaching reagents, this research provided a more sustainable methodology to utilize lignocelluloses to design robust aerogels to deal with the leakage of oil and organic solvents in industrial applications. Graphical abstract: Unlabelled Image Highlights: LCNF was produced from Miscanthus using citric acid and mechanical fibrillation. LCNF aerogels were prepared by gas phase coagulation and diisocyanate modification. LCNF aerogels had high water contact angle and enhanced compression properties. LCNF aerogels exhibited absorption performance for various organic solvents.